The Influence of Motivation and Empowerment on Employee Performance with Organizational Commitment as a Mediator (Study on Employees of the Empowerment and Village Affairs Agency, Batang Regency) - Sutiksan, Sutiksan; Rifai, Alimuddin Rizal (Universitas Syiah Kuala, 2025)
This study aims to analyze the effect of motivation and empowerment on employee performance with organizational commitment as a mediating variable among village officials in Batang Regency. The research employed a quantitative method with a survey approach involving 140 respondents selected using a census method. Data were collected through a 7-point Likert scale questionnaire and analyzed using SPSS. The results indicate that both motivation and empowerment have a positive and significant impact on employee performance, directly and indirectly through organizational commitment. These findings highlight the importance of enhancing motivational factors and empowerment to develop committed and high-performing personnel in the village government setting. Organizational commitment is proven to act as a partial mediator, strengthening the relationship between the independent variables and employee performance. This research provides practical implications for local governments in improving public service quality through more participatory and empowering human resource management strategies.